Estimating the Potential Effects of a Vaccine Program Against an Emerging Influenza Pandemic—United States. (10th April 2015) - Biggerstaff, Matthew; Reed, Carrie; Swerdlow, David L.; Gambhir, Manoj; Graitcer, Samuel; Finelli, Lyn; Borse, Rebekah H.; Rasmussen, Sonja A.; Meltzer, Martin I.; Bridges, Carolyn B.
Abstract : Background. Human illness from influenza A(H7N9) was identified in March 2013, and candidate vaccine viruses were soon developed. To understand factors that may impact influenza vaccination programs, we developed a model to evaluate hospitalizations and deaths averted considering various scenarios. Methods. We utilized a model incorporating epidemic curves with clinical attack rates of 20% or 30% in a single wave of illness, case hospitalization ratios of 0.5% or 4.2%, and case fatality ratios of 0.08% or 0.53%. We considered scenarios that achieved 80% vaccination coverage, various starts of vaccination programs (16 or 8 weeks before, the same week of, or 8 or 16 weeks after start of pandemic), an administration rate of 10 or 30 million doses per week (the latter rate is an untested assumption), and 2 levels of vaccine effectiveness (2 doses of vaccine required; either 62% or 80% effective for persons aged <60 years, and either 43% or 60% effective for persons aged ≥60 years). Results. The start date of vaccination campaigns most influenced impact; 141 000–2 200 000 hospitalizations and 11 000–281 000 deaths were averted when campaigns started before a pandemic, and <100–1 300 000 hospitalizations and 0–165 000 deaths were averted for programs beginning the same time as or after the introduction of the pandemic virus. The rate of vaccine administration and vaccine effectiveness did not influence campaign impact as much as timing of the start of campaign. Conclusions. Our findings suggest that efforts to improve the timeliness of vaccine production will provide the greatest impacts for future pandemic vaccination programs.